Identifikasi Sumber Pendapatan Asli Daerah pada Pajak Daerah Kota Jambi - Iqra Wiarta; Rahmi Handayani; Arman Syafa`at; Aulia Yunica Harly (J-MAS (Jurnal Manajemen dan Sains), 2021)
The focus of this research is to identify the original source of income in jambi city area, one of which is local taxes. Local taxes are an option in this study due to its enormous contribution to the original income of the region in the city of Jambi. This research aims to find out how much local tax growth, the effectiveness of local taxes, its contribution to the original income of the jambi city area and the classification of local taxes based on overlay theory. The method used is quantitative descriptive with data using secondary data. The results of the study showed the average growth of jambi city tax from 2018 to 2019 at 19.54%, with a contribution of 65.05%. The level of total local tax effectiveness is very effective in 2018 and 2019. The identification results showed that of the 9 (nine) regional tax sources 6 (six) were categorized as prime, 2 (two) potential and 1 (one) backward.